A FAPESP E A CIÊNCIA DA COMUNICAÇÃO: LEGITIMAÇÃO, CONTRIBUIÇÃO E CONSTRUÇÃO DA ÁREA - GABRIOTI , RODRIGO (2018)
The work considers 912 projects derived from scholarships and research assistances supported by Foundation for Research Support of São Paulo’s State (FAPESP) between 1992 and 2016 in the Communication Field. From them, we offer to do the taxonomy construction for check your contributions to legitimate the knowledge having as horizon a development agency. Through the FAPESP’s Virtual Library, we study the existing production. There are two main methodological strategies: by the quantitative analysis, the samples were collected and divides into seven categories on which it was possible to establish the percentages that provide, for example, study tendencies and established academic relations. By the Content Analysis, the analyzed documents are related to the problem raised on the role of fomentation in the taxonomic construction of studies in Communication applying the method of inferences in the instances of emission, message, signification and means for the indentation of indices and indicators that represent general data constituted from of the universe of development lines. Then, we show that the Communication Research is attractive and is centralized at São Paulo city presenting modernization signs in your objects in the first secular passage of its studies; it is still detaining a conceptual and disciplinary conceptual impasse; it needs a meta search like this that considers FAPESP to think about what is writed and is produced at Brazilian Communication’s Postgraduate as an attempt to remove the Field Studies from your institutional strength for a n autonomous, legitimized and recognized thinking.